The Meaningful Tourism Paradigm – A Tool for Sustainable Tourism Development in Times of Crises and Challenges - Arlt, Wolfgang Georg (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
Confronted by converging crises – climate change, AI-driven disruption, and shifting traveler demands – traditional sustainable tourism models struggle with "sustainability fatigue," often emphasizing sacrifice over tangible gain. This article introduces the Meaningful Tourism (MT) paradigm as a transformative tool for resilient development. Grounded in Positive Psychology, MT ensures the objective benefits and subjective satisfaction of all six core stakeholders (Visitors, Host Community, Employees, Businesses, Governments, Environment) simultaneously. It rejects zero-sum trade-offs, instead fostering aligned stakeholder interests through achievable, annually measured SMART KPIs tracking transparent progress. By shifting focus from restriction to mutual flourishing and demonstrable outcomes, MT provides a practical, positive, and holistic framework for building sustainable tourism resilience in an era defined by challenges and the search for meaning.